1997
DOI: 10.1152/ajpgi.1997.273.2.g314
|View full text |Cite
|
Sign up to set email alerts
|

Gut ischemia and mesenteric synthesis of inflammatory cytokines after hemorrhagic or endotoxic shock

Abstract: The intestine plays a major role in the pathophysiology of multiorgan failure. Although the systemic inflammatory response might be induced by endotoxin released through bacterial translocation, other factors such as intestinal ischemia might be implicated. We investigated the relationship between intestinal ischemia-reperfusion and cytokine release in rat models of hemorrhagic or endotoxic shock. Plasma levels of tumor necrosis factor-alpha (TNF-alpha), interleukin-6 (IL-6), lactate, and endotoxin, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 0 publications
2
60
0
3
Order By: Relevance
“…Many associated pathophysiologic phenomena have been studied, some of which have been implicated as possible mediators of the extra-intestinal organ dysfunction seen during progression of SIRS to multiple organ failure (MOF) (5,6). Areas currently under investigation include the activation of local immune cells (7), alteration of intestinal permeability with subsequent bacterial translocation (8), changes in the local-regional production of inflammatory mediators (9), production of reactive oxygen species (10), changes in coagulation (11), and alteration in the expression of cellular adhesion molecules (12). Despite the extensive efforts in this field of study, the proximal cause of MOF secondary to IIR-induced SIRS has yet to be clearly elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Many associated pathophysiologic phenomena have been studied, some of which have been implicated as possible mediators of the extra-intestinal organ dysfunction seen during progression of SIRS to multiple organ failure (MOF) (5,6). Areas currently under investigation include the activation of local immune cells (7), alteration of intestinal permeability with subsequent bacterial translocation (8), changes in the local-regional production of inflammatory mediators (9), production of reactive oxygen species (10), changes in coagulation (11), and alteration in the expression of cellular adhesion molecules (12). Despite the extensive efforts in this field of study, the proximal cause of MOF secondary to IIR-induced SIRS has yet to be clearly elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple organ failure, including acute lung injury (ALI), is a common complication of intestinal ischemia/reperfusion (I/R) injuries and contributes to its high mortality rate (2). ALI is caused by a systemic inflammatory response due to the release of proinflammatory cytokines and bacteria-derived endotoxins from reperfused ischemic tissue (3)(4)(5)(6). Only a limited number pharmacologic treatment options have been found that provide some benefit in I/R and ALI, most of them targeting inflammatory mediators and oxidative stress pathways (7).…”
mentioning
confidence: 99%
“…20 During systemic inflammatory response syndrome and the compensatory anti-inflammatory response syndrome, the immune function may be impaired. [21][22][23][24] Individuals with immunity abnormalities such as ICU patients, who had been previously infected with T. gondii, may show increased IgG antibody titres or less frequently, increased titres of acute-phase antibodies, which may be interpreted as reactivation. T. gondii infection produces IgM, IgA, IgE and IgG antibodies, with the first three being detected early during the course of infection.…”
Section: Discussionmentioning
confidence: 99%